Infrastructures as a future project for a city? Some considerations about Burgos, medium-size city of Castilla y León (Ciudades, 2017)
Infrastructures, in recent years, are not just simple artifacts that make urban life easy. In fact, infrastructures have exceeded their original functions becoming relevant in the new public policies. Roads, railways, airports, industrial states are designed nowadays as genuine city projects. Being able, by themselves, not only to sustain the morphological structure and the identity of each city, but also to induce its economic growth, improve its labour market and, finally, increase its welfare state. However, are these infrastructures per se a reliable project for a city? How are treated these structures in the current Spanish urban planning? How are sectorial policies that depended of such infrastructures conditioning this urban planning? Is there any future for a city with -no infrastructure-? This article proposes some views on the subject in relation to the medium-size city of Burgos, which is supporting a notably growth process and urban transformation linked directly to the accomplishment of pertinent infrastructures.
Keywords: urban infrastructures; medium-size cities; city project; road; railway; airport; industry; Burgos